2009
DOI: 10.1007/s10725-009-9375-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ABA on primary terpenoids and Δ9-tetrahydrocannabinol in Cannabis sativa L. at flowering stage

Abstract: This work examined the effects of exogenously applied abscisic acid (ABA) on the content of chlorophyll, carotenoids, a-tocopherol, squalene, phytosterols, D 9 -tetrahydrocannabinol (THC) concentration, 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) and 1-deoxy-D-xylulose 5-phosphate synthase (DXS) activity in Cannabis sativa L. at flowering stage. Treatment with 1 and 10 mg l -1 ABA significantly decreased the contents of chlorophyll, carotenoids, squalene, stigmasterol, sitosterol, and HMGR activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…Positive effects of ABA in increasing of chlorophyll content have been reported by Agarwal et al (2005). At previous work we found that at flowering stage ABA decreased the chlorophyll content in both male and female Cannabis plants (Mansouri et al 2009). This result indicates that plant response to ABA is different at various stages of development.…”
Section: ⎯⎯⎯⎯supporting
confidence: 57%
See 2 more Smart Citations
“…Positive effects of ABA in increasing of chlorophyll content have been reported by Agarwal et al (2005). At previous work we found that at flowering stage ABA decreased the chlorophyll content in both male and female Cannabis plants (Mansouri et al 2009). This result indicates that plant response to ABA is different at various stages of development.…”
Section: ⎯⎯⎯⎯supporting
confidence: 57%
“…Chlorophyll and carotenoids in leaves were determined as described by Lichtenthaler (1987), and α-tocopherol was extracted according to Panfili et al (2003) and analyzed as described previously (Mansouri et al 2009). Quantitative analysis of squalene and phytosterols (campesterol, β-sitosterol and stigmasterol) followed the procedure of Hartmann and Benveniste (1987).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
See 1 more Smart Citation
“…ABA (synthesized via the MEP pathway) has been found to induce the biosynthesis of MEP-derived metabolites, and both ABA-dependent and -independent signaling pathways appear to be involved in osmotic stress tolerance (Huang et al, 2012). GA 3 has been reported to inhibit the biosynthesis of MEP-derived isoprenoids and to stimulate the MVA pathway (Mansouri et al, 2009). Additionally, ROS also could play the role of such regulators, since their signaling network controls diverse stress responses (Lin and Aarts, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…ABA can activate the SnRK2 protein, which phosphorylates downstream transcription factors and allows the corresponding genes to be expressed (Shan et al 2012). Moreover, Mansouri et al (2009) have discovered that ABA enhances the activity of 1-deoxy-D-xylulose 5-phosphate synthase, which is another essential enzyme in the MEP pathway. Therefore, ABA and GA simultaneously increase the expression of HMGR and DXR as well as their corresponding enzyme activities, which subsequently promote essential oil synthesis in A. lancea.…”
Section: Discussionmentioning
confidence: 99%